Liquid metal embrittlement of 12Cr ferritic/martensitic steel thin-walled tubes exposed to liquid lead-bismuth eutectic. (February 2022) - Wang, Hao; Gong, Xing; Xiao, Jun; Chai, Linjiang; Yu, Zhiyang; Chen, Haitao; Zhao, Ke; Zhou, Jun; Liu, Guiliang; Chen, Yong; Qiu, Shaoyu
Abstract: In this work, liquid metal embrittlement (LME) susceptibility of 12Cr ferritic/martensitic (F/M) thin-walled tubes has been tested in liquid lead-bismuth eutectic (LBE) under different temperatures (i.e., 350, 400 and 450 °C), oxygen concentrations (i.e., oxygen-poor and oxygen-saturated) and strain rates (i.e., 5 ×10 −5, 1 ×10 −6 and 5 ×10 −7 s −1 ). The results show that LME occurs under nearly all the testing conditions, and the most influential factors upon the LME susceptibility are oxygen concentration and strain rate. Transmission electron microscopy (TEM) characterization at crack tips shows that LME cracks propagate preferentially along microstructural boundaries, such as martensite lath boundaries, subgrain boundaries and carbides/lath interphase boundaries. Highlights: 12Cr F/M steel thin-walled tubes are sensitive to LME. LME cracks initiate either at inner or outer tube surface. Lower oxygen dissolved in LBE and slower strain rate promote LME. LME cracks propagate preferentially along microstructural boundaries.